Design, Synthesis and Evaluation of a Novel Teoptinib Derivative as an Effective Anti-hepatocellular Carcinoma Agent - Yu, Huijuan; Zhang, Xiaodong; Li, Jiayu; Wang, Kaimei; Yin, Changjun; Li, Xinshu; Li, Lianyun; Shao, Guang; Jin, Shaowen (Current Pharmaceutical Design, 2024)
Background & Purpose: Hepatocellular Carcinoma (HCC) is a type of liver cancer known for its poor prognosis and high mortality. Teoptinib is a highly selective MET inhibitor that has been used in the treatment of liver cancer. Although good progress has been made in clinical treatment, further improvement is still needed. In this study, a series of novel Teoptinib derivatives were synthesized and evaluated as anti-cancer agents for the treatment of liver cancer, and an oral nanodrug delivery system was also explored. Methods: A series of novel Teoptinib derivatives were synthesized, and an oral nanodrug delivery system was also explored. HPLC, high-resolution mass spectrometer and NMR were used to determine the structure and molecular formula of the synthesized compounds. Zeta potential assay was used to access the particle size distribution and zeta potential of the nanoparticles. MTT assay, cell colony formation assay, cell apoptosis inhibition assay, cell scratch assay, and the MHCC-97H xenograft model of nude mice assay were used to evaluate the in vitro and in vivo anti-tumor activity of the synthesized compounds. Results: Compound (R)-10 showed the best antitumor activity with 0.010 μM of the IC50 value against MHCC-97H, a human liver cancer cell line with high c-Met expression. The MHCC-97H xenograft model of nude mice assay showed that nano-prodrug of compound (R)-10 exhibited good in vivo activity with 87.67% of the TGI at the dosage of 8 mg/kg. Conclusion: We designed and synthesized a series of c-Met inhibitors containing different side chains and chiral centers as anti-liver cancer agents. Among them, compound (R)-10 shows a promising effect as a lead molecule for further study in the treatment of liver cancer. The successful incorporation of (R)-10 into a novel oral nanodrug delivery system highlights the importance of effective drug delivery systems for enhanced therapeutic efficacy.
Keywords: c-Met inhibitor